2014
DOI: 10.1089/aid.2013.0270
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years Survey of Primary HIV-1 Resistance in Serbia: The Occurrence of Multiclass Resistance

Abstract: In Serbia, the first cases of HIV infection were reported in 1985, whereas antiretroviral (ARV) therapy has been in use since 1987. With this study we aimed to assess the occurrence and pattern of HIV resistance mutations among newly diagnosed patients in the period 2002-2011. The study prospectively included 181 adult patients. Genotypic HIV-1 drug resistance testing was performed and drug resistance was scored according to the 2009 WHO list for surveillance of drug resistance mutations (SDRMs). A bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…In contrast, Slovenia, which is a small central European country with a population of 2 million, had a historically low TDR prevalence (i.e., 4.7% TDR among HIV-1 positive individuals diagnosed from 2005 to 2010), which is similar to the rates reported from some Balkan countries; for example, from Bulgaria (5.2%), Serbia (8.8%), and Greece (6.0%) [ 5 , 9 11 ].…”
Section: Introductionsupporting
confidence: 58%
“…In contrast, Slovenia, which is a small central European country with a population of 2 million, had a historically low TDR prevalence (i.e., 4.7% TDR among HIV-1 positive individuals diagnosed from 2005 to 2010), which is similar to the rates reported from some Balkan countries; for example, from Bulgaria (5.2%), Serbia (8.8%), and Greece (6.0%) [ 5 , 9 11 ].…”
Section: Introductionsupporting
confidence: 58%
“…Previous molecular studies of Serbian HIV epidemic identified subtype B as the dominant HIV-1 type, present in over 90% of individuals diagnosed between 1997 and 2011 (Stanojevic et al, 2002, 2014; Siljic et al, 2013; Magiorkinis et al, 2016). Clusters related HIV-1 transmission was observed, in particular among MSM transmission group and linked to high prevalence of concomitant sexually transmitted infections (STIs) (Siljic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the available repertoire of antiretroviral drugs fully covered by the national health insurance system remains rather limited [14] . Currently, therapeutic options available in Serbia for initial HIV treatment include zidovudine, lamivudine, and abacavir among the NRTIs; nevirapine and efavirenz among the non-NRTIs; and saquinavir, fosamprenavir, and lopinavir/ritonavir among the protease inhibitors.…”
Section: Discussionmentioning
confidence: 99%